The Structure of Eukaryotic and Prokaryotic Complex I - Clason, T. (2009)
The structures of the NADH dehydrogenases from Bos taurus and Aquifex aeolicus have been determined by 3D electron microscopy, and have been analyzed in comparison with the previously determined structure of Complex I from Yarrowia lipolytica. The results show a clearly preserved domain structure in the peripheral arm of complex I, which is similar in the bacterial and eukaryotic complex. The membrane arms of both eukaryotic complexes show a similar shape but also significant differences in distinctive domains. One of the major protuberances observed in Y. lipolytica complex I appears missing in the bovine complex, while a protuberance not found in Y. lipolytica connects in bovine complex I a domain of the peripheral arm to the membrane arm. The structural similarities of the peripheral arm agree with the common functional principle of all complex Is. The differences seen in the membrane arm may indicate differences in the regulatory mechanism of the enzyme in different species.